Issues of Historicity, Succession, and Modernity In Socio-Civilizational Development - Dildora Danil Qizi Qoraboyeva (Pubmedia Social Sciences and Humanities, 2026)
This article analyzes the continuity and contradictory nature of socio-civilizational development from the perspective of concepts of historicity, continuity, and modernity. Historicity is illuminated as the need to take into account the past stages of civilization and to critically review experience. It is argued that the continuity of traditions, cultural codes, and intergenerational connections can lead to long-term civilizational silence, while total negation can lead to the loss of identity. Modernity is analyzed as issues of adaptation to the near future in the context of globalization, technogenic transformation, and changes in values. The article examines the contradictions between historicity, continuity, and modernity, as well as the mechanisms of their emergence, using various civilizations as examples.